2001
DOI: 10.1198/016214501753168217
|View full text |Cite
|
Sign up to set email alerts
|

Are Points in Tennis Independent and Identically Distributed? Evidence From a Dynamic Binary Panel Data Model

Abstract: This article tests whether points in tennis are independent and identically distributed (iid). We model the probability of winning a point on service and show that points are neither independent nor identically distributed: winning the previous point has a positive effect on winning the current point, and at "important" points it is more dif cult for the server to win the point than at less important points. Furthermore, the weaker a player, the stronger are these effects. Deviations from iid are small, howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
126
1
5

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(142 citation statements)
references
References 33 publications
3
126
1
5
Order By: Relevance
“…First, we assume that points are i.i.d., so that p a and p b stay xed during the match. As we h a ve demonstrated in Klaassen and Magnus (2001), points are not i.i.d., but the deviations from i.i.d. are small, so that in particular applications (such as forecasting) the i.i.d.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, we assume that points are i.i.d., so that p a and p b stay xed during the match. As we h a ve demonstrated in Klaassen and Magnus (2001), points are not i.i.d., but the deviations from i.i.d. are small, so that in particular applications (such as forecasting) the i.i.d.…”
Section: Resultsmentioning
confidence: 99%
“…We brie y summarize the estimation procedure, which follows Klaassen and Magnus (2001), specialized to the situation where all points are i.i.d.…”
Section: Estimation Of P a + P B Based On Point Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, Klaassen and Magnus (2001) show that the probability of winning a point is not independent from who won the previous point, and that some points and F o r P e e r R e v i e w notation for match and tournament, and let the utility of a player be additively separable in the utility derived from winning the stage price and the disutility of exerting effort,…”
Section: Derivation Of Testable Hypothesesmentioning
confidence: 99%
“…First, the same reasoning suggests that there could be a motivational benefit to succeeding on fourth down, and thus that the analysis could understate the benefits of a successful fourth-down attempt. Second, studies of momentum in other sports have found at most small momentum effects (e.g., Gilovich, Vallone, and Tversky 1985;Albright 1993;Klaassen and Magnus 2001).…”
Section: Momentummentioning
confidence: 99%